Effect of Stock Control on Performance of Small-Scale Business Enterprises: A Case Study of Kabale Municipality Kabale District. - Tuheisomwe, Quilino (Kabale University, 2024)
This study focused on stock control and the performance of small-scale business enterprises in Kabale District, specifically within Kabale Municipality. The research was guided by three main objectives: to identify factors that improve stock control and business performance in small-scale enterprises, to explore inventory control methods applicable to these businesses, and to determine the relationship between stock control and business performance. A descriptive survey design was used, well-suited to examining the relationship between stock control and performance, estimating outcomes, and making predictions. The study population included all elements from which inferences were drawn. Data was gathered from company records in annual reports and accounts over selected periods, supporting the research objectives. Data collection involved both primary and secondary sources, utilizing questionnaires and interview guides. The study recommends that business firms periodically reassess their goals and incorporate constructive feedback. While inventory control is essential for business growth, challenges like procurement delays, frequent stockouts, storage costs, and bank loans affect inventory management and overall performance. This study aimed to address this gap by examining the impact of inventory control on the performance of small-scale businesses in Kabale Municipality, Kabale District.